Soldiers of the nation : military service and modern Puerto Rico, 1868-1952 - Franqui-Rivera, Harry (Studies in war, society, and the military., 2018)
"An exploration of the military and political mobilization of popular sectors of Puerto Rican society as the island transitioned from Spanish to U.S. imperial rule."--Provided by publisher